Multiphase flow regulation of PDMS microfluidic chips - Choong, Darryl Zhi Yong (Nanyang Technological University, 2024)
Microfluidics have uses across many disciplines as they enable the manipulation of miniscule yet precise amounts of fluids, from cell analysis, point-of-care testing to lab-on-a-chip. In this study, polydimethylsiloxane (PDMS) microfluidic chip is used to generate water-in-oil (W/O) emulsions. The fabricated chip was then used to test the varying effects of different inner and outer flowrates with two immiscible fluids, the dispersed phase of 15% glycerol and 5% PF127 in water and continuous phase of 1 wt% FluoSurf in FC-40. Depending on the flowrate of the two phases, the diameters of the emulsions can range from 50μm to 100μm. The frequencies at which the emulsions are produced would also vary, with the lowest frequency at 30Hz and the highest frequency at 275Hz. The flow regimes also change with the varying flowrates of the two phases, but in general, all tested parameters would have flow regimes that changes from dripping to parallel flow. The developed procedures and subsequent testing and results of the experiments can provide with a better understanding of a scalable preparation method and the effects of varying flowrates and their applications.